2021
DOI: 10.1021/jacs.1c04037
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Divergent Synthesis of a High Aspect Ratio Carbon Nanobelt

Abstract: Carbon nanobelts are molecules of high fundamental and technological interest due to their structural similarity to carbon nanotubes, of which they are molecular cutouts. Despite this attention, synthetic accessibility is a major obstacle, such that the few known strategies offer limited structural diversity, functionality, and scalability. To address this bottleneck, we have developed a new strategy that utilizes highly fused monomer units constructed via a site-selective [2 + 2 + 2] cycloaddition and a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 44 publications
(71 reference statements)
0
58
0
Order By: Relevance
“…Nevertheless, the first example of this family, a segment of an armchair [6,6]­CNT, was reported in 2017 . Soon after that, several CNBs with different sizes and edge structures were successfully isolated . In addition, CNBs containing heteroatoms and nonhexagonal rings were also prepared.…”
mentioning
confidence: 99%
“…Nevertheless, the first example of this family, a segment of an armchair [6,6]­CNT, was reported in 2017 . Soon after that, several CNBs with different sizes and edge structures were successfully isolated . In addition, CNBs containing heteroatoms and nonhexagonal rings were also prepared.…”
mentioning
confidence: 99%
“…Very recently, Tilley and co‐workers reported a new synthetic strategy for the synthesis of new carbon nanobelts (CNBs). Starting from highly fused monomers and using a site‐selective [2+2+2] cycloaddition with Cp 2 (py)Zr(η 2 ‐Me 3 SiC 2 SiMe 3 ), a high‐yielding macrocyclization was realized on large scale [12c] . The authors concluded that this synthetic method constitutes a general principle for greater synthetic efficiency.…”
Section: Substitution Of Me3sic2sime3 By Substrates Coupling Reaction...mentioning
confidence: 99%
“…1a), which has a cavity shaped like a Celtic cross. The recently revived interest in the synthesis of carbon nanobelts, 11–13 particularly, the efforts to synthesize zigzag carbon nanobelts 14–16 by Diels–Alder reactions 17–20 gave rise to new members of oxanorbornene-fused double-stranded macrocycles, 21 such as 1 17 and 2 20 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%